Kebebasan Beragama dan Kontroversi Hijab : Sebuah Perspektif Hak Asasi Manusia - Putra, Wiene Surya (Jurnal Landraad, 2023)
This article investigates the position of international human rights law with respect to the Hijab (veil) worn by Muslim women to express their religious beliefs. In Islam, the hijab is not only an important aspect of a woman's faith, but also shows their religious affiliation as a form of submission to God. However, the regulation of headscarves in several countries has raised complex human rights issues, particularly in the context of women's rights to freedom of religion and its manifestations, equality and non-discrimination. This article examines the theological status of the hijab in Islam for the first time. In the West, the ban on wearing the headscarf has increased discrimination against Muslim women and restricted the movement of Muslim women as they are forced to withdraw from public life and remain at home. Secondly, it analyzes the selected laws, administrative acts, and cases regarding the wearing of the hijab in public places, especially in European Union (EU) countries. The article concluded that there was no justification under international human rights law for banning Muslim women from wearing the headscarf. The absence of a reasonable justification in accordance with human rights law can interfere with individual freedom to practice a religion. The general exclusion of women from work or other life activities due to the use of the headscarf will lead to further discrimination. The article concluded that there was no justification under international human rights law for banning Muslim women from wearing the headscarf. The absence of a reasonable justification in accordance with human rights law can interfere with individual freedom to practice a religion. The general exclusion of women from work or other life activities due to the use of the headscarf will lead to further discrimination. The article concluded that there was no justification under international human rights law for banning Muslim women from wearing the headscarf. The absence of a reasonable justification in accordance with human rights law can interfere with individual freedom to practice a religion. The general exclusion of women from work or other life activities due to the use of the headscarf will lead to further discrimination.